A Retrospective Study Using a Novel Body-Shift Implant Design with a Novel Alloplastic Particulate Grafting Material in Immediate Extraction Sockets - O'Hooley, Dominic B.; Nicolopoulos, Costa; Worthing, Mark G.; Yuvanoglu, Petros; Melas, Fotis; Fairbairn, Peter J. M.; Kurtzman, Gregori M. (European Journal of Dentistry, 2025)
With resurgence in immediate tooth replacement therapy (ITRT) as a method of preserving both hard and soft tissues for improved aesthetic outcomes, this multicenter, prospective study looked at two novel products and their effect on those outcomes. Thirty-one maxillary single-tooth implants were included, of these 54.8% were central incisors, 25.8% lateral incisors, and 19.4% canines. Three complications were reported; one case nondraining fistula, one case a nonseated provisional restoration, and one case a fractured zirconia abutment. The definitive restorations were delivered between 4 hours and 18 months postimplant placement and all restorations were screw-retained. ITRT is frequently utilized when a tooth to be extracted will be replaced by an implant aiding in preservation of the hard and soft tissue that may be lost due to resorption during healing of the extraction socket. The narrower neck region of the Inverta implant results in thicker crestal bone around the implant, where loading under function occurs. Grafting that area around the implant at placement with EthOss results in more predictable bone stability in the long term.
Keywords: novel implant design; alloplastic graft materials; immediate tooth replacement